Fiscal Councils: The UK Office for Budget Responsibility. - Wren-Lewis, S (CESifo-Group, 2011)
One of the most recent fiscal councils to be formed is the Office for Budget Responsibility (OBR) in the UK. It is distinctive in two respects. First, it provides the macroeconomic and budgetary forecasts on which government fiscal decisions are based. Second, it is not allowed to consider anything other than current government policy. To understand why the OBR has this specialised remit, we begin by examining the circumstances that led to its creation. After outlining its tasks in more detail, we then consider issues related to forecasting, policy analysis and independence.